Analisis Isi Pesan Colorism Pada Tayangan Channel Youtube Gitasav Berjudul "Ketika Warna Kulit Bikin Hidup Sulit" | Beropini Episode 59 - Dessi Isnaeni; Rachmawati Windyaningrum; Faisal Reza (In Search (Informatic, Science, Entrepreneur, Applied Art, Research, Humanism), 2021)
Colorism is the different manner that a person gets based on skin color. This research aims to find out how many messages contain colorism messages on YouTube channel Gitasav entitled "Ketika Warna Kulit Bikin Hidup Sulit" | Beropini Episode 59. This research uses content analysis of the Holsty model theory and Lasswell theory. This research uses quantitative methods through descriptive content analysis design. This research uses descriptive statistics that aim to describe how many colorism messages appear on these impressions. The results of this research indicate that there are messages of colorism on YouTube channel Gitasav entitled "Ketika Warna Kulit Bikin Hidup Sulit" Beropini| Episode 59 with a total frequency of 227 times(100%). There are colorism messages in the lighter skin color message category with a total frequency of 73 times (32.1%). There are colorism messages in the whiter skin color message category with a total frequency of 40 times (17.6%). There are messages of colorism in the darker skin color message category with a total frequency of 45 times (20%). There are messages of colorism in the browner skin color message category with a total frequency of 22 times (9.7%). There are messages of colorism in the category of psychological and economic privilege messages for light skin with a total frequency of 35 times (15.4%). There are messages of colorism in the low social and economic hierarchical message category for dark skin with a total frequency of 12 times (5.2%). It can be concluded that there are messages colorism in each message category colorism on YouTube content Gitasav.